The burden and correlates of bloodborne pathogens in a Zambian Blood Donor Cohort - Mwila Mapipo; Alex Maleti; Phinnoty Mwansa; Paul Daka; David Chisompola (PLoS ONE, 2026)
Introduction Transfusion is a critical life-saving intervention, but the safety of the blood supply remains a major public health concern, particularly in sub-Saharan Africa, due to the risk of transfusion-transmitted infections (TTIs). This study aimed to determine the burden and correlates of bloodborne pathogens among blood donors in Muchinga Province, Zambia. Methods A cross-sectional study was conducted using records from 2,667 blood donors at the Chinsali General Hospital Blood Bank between January and December 2021. Data on demographic characteristics, donation type, and ABO/Rhesus blood group were collected. Screening for Hepatitis B (HBV), Hepatitis C (HCV), HIV, and Syphilis was performed using the Abbott Alinity i platform. Logistic regression was used to identify factors associated with infection status. Results The overall prevalence of TTIs among donors was 25.7% (686/2,667). The most prevalent single infections were HBV and Syphilis 8.0% (213/2,667), followed by HCV 7.8% (207/2,667), and HIV 7.7% (206/2,667), with notable co-infection rates, particularly HIV/Syphilis (4.9%). In the composite multivariable analysis, donors with blood group O had 36% lower adjusted odds of any TTI compared to those with blood group A (AOR = 0.64; 95% CI: 0.52–0.79; p < 0.0001) and individuals aged over 45 years had 45% higher adjusted odds of TTIs compared to those aged 16–24 years (AOR = 1.45; 95% CI: 1.04–2.00; p = 0.026). Furthermore, multivariable pathogen-specific analyses revealed distinct risk profiles: donors aged ≥45 years had significantly higher odds of syphilis (AOR = 2.38; 95% CI: 1.49–3.80; p < 0.0001), female sex was associated with lower odds of HBV (AOR = 0.69; 95% CI: 0.52–0.93; p = 0.016), blood group O was protective against HCV (AOR = 0.49; 95% CI: 0.35–0.69; p < 0.0001), and donors from Mpika district had higher odds of HIV (AOR = 1.82; 95% CI: 1.03–3.21; p = 0.037). Conclusion This study highlights a substantial burden of TTIs among blood donors and identifies blood group O as a potential protective factor, suggesting a potential biological basis that requires further study. Strengthened donor screening and public health interventions are critical to improving blood safety.